(untitled) - Jones, Leo (Cambridge, 2000)
Introduction to the BEC Vantage exam and a full practice test including audio
Keywords: Business communication,Business English,Giao tiếp thương mại,Ngôn ngữ tiếng Anh; English language,Anh văn thương mại